Factors Influence Side effects of the Standard Short-Course Anti-tuberculosis Drugs among New Patients : 6th Office of Disease Prevention and Control,Khon Kaen Province - เทศนา นงลักษณ์; บุตรสอน อารี; มุ่งเขตกลาง วิวรรธน์ (Disease Control Journal, 2007)
The retrospective study aimed to determine factors influenced side-effect of anti-tuberculosis drugs (Cat.1_2HRZE/4HR) among 219 new pulmonary tuberculosis patients both positive and negative acid fast bacilli smeared examinations registered between 2005-2006 at the 6th Office of Disease Prevention and Control, Khon Kaen Province, Thailand. The variables were analyzed by logistic regression. The results were the patient’s age less than and equal 45 years influenced the occurred of side effects more than the patient’s age more than 45 years (AOR = 2.04, 95% CI = 1.06-3.94), the single separated drugs regimen occurred side effects more than fixed dose combination drugs regimen (AOR = 2.01, 95% CI = 1.09-3.69), the occupation as employee and officer occurred side effects less than the occupation as farmer (AOR = 0.17, 95% CI = 0.05-0.52 and AOR = 0.34 95% CI = 0.17-0.69) and married status influenced the occurred of side effects more than single status (AOR= 2.22 95% CI = 1.05-4.70)